Commentary on "Aesthetic Experience Explained by the Affect-Space Framework" by E. Schubert, A. C. North, & D. J. Hargreaves - Brattico, Elvira (Empirical Musicology Review, 2017)
This commentary discusses the paper by Schubert and colleagues in the context of the recent proposals in the field of empirical aesthetics and neuroaesthetics, emphasizing the need for inclusion of the time variable for accounting for the dynamic nature of a musical experience. At the same time, the efforts of the authors for systematizing the concepts in the field are praised.